Analysis of The Nature of Science in Chemistry Textbooks on The Topic Acid-Base Equilibrium: a Content Analysis - Rahmah, Aulia; Ariani, Sri Retno Dwi; Mulyani, Bakti (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
This study was conducted to describe aspects of the Nature of Science (NoS), its presentation, and its scores from chemistry textbooks used in Surakarta on acid-base equilibrium topics. This research was qualitative research with a content analysis method. Three high school chemistry textbooks for class XI from different publishers were analyzed by two raters based on ten aspects of the NoS. Interrater reliability was calculated using the cohen Kappa. The results showed that a scientific law is the only aspect that is not included in the three textbooks A, B, and C. Other aspects of NoS contained in textbooks A and B are slightly different from textbook C. Textbooks A and B contain the same aspects: empirical, inferential, creative, theory-driven, tentative, scientific methods, scientific theories, social science, and the application of science in socio-cultural, while textbook C does not contain tentative and theory-driven aspects. The implicit-correct category dominates the presentation of the NoS aspects in the textbooks. Presentations with implicit-incorrect and explicit-incorrect categories were not found in this study. The scores obtained by textbooks A, B, and C based on the presentation of aspects of NoS are 9, 11, and 8, respectively, of the maximum total score that can be obtained of 30. It did not show the presence of the NoS aspects explicitly, correctly, consistently, and completely, so textbooks containing NoS explicitly are required. Teachers also need to guide students in interpreting NoS in learning.